Analisis Rantai Pasok Komoditas Cengkih Hutan di Maluku - Kembauw, Esther; Mahulette, Asri Subkhan; Wattimena, Anna Yuliana; Senewe, Rein Estefanus (Journal of Agricultural Socio-Economics (JASE), 2021)
The Maluku Islands are renowned as the world's clove origin. Maluku is home to one of the indigenous clove germplasms known as Forest cloves. Forest Cloves are wild-type cloves found on Ambon Island, Maluku. The study's objective was to conduct an analysis of the supply chain for forest clove commodities. The investigation was conducted in the villages of Hitulama, Hitumesing, and Pulau Seram in Maluku Province, as well as in the villages of Latu and Hualoi. Primary data were collected from a sample of 25 forest clove farmers. The data analysis reveals that several parties are involved in the supply chain of Maluku's forest clove commodities, including farmers/suppliers, village-level middlemen, large collectors in the Regency City and provincial capital, Ambon City, as well as large companies in Surabaya that use forest cloves as raw material. Efforts to conserve forest cloves must be made in order to expand local potential and farmers' revenue. As a result, the wealth of Forest clove germplasm in Maluku province can be increased.